Fabrication of Cu(ii) based halobenzoate appended ladder polymers with efficient charge transport properties. Issue 40 (25th September 2020) - Islam, Sakhiul; Pal, Baishakhi; Khan, Samim; Maity, Suvendu; Naaz, Sanobar; Ghosh, Prasanta; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : Two novel 1D Cu(ii ) CPs based on halo-substituted benzoate ligands together with an N-donor bpe spacer ligand exhibit high electrical conductivity and reveal Schottky diode behaviour. Abstract : Two isotypical Cu(ii ) based one-dimensional coordination polymers (1D CPs) [Cu2 ( p -clba)4 (bpe)2 Cu( p -clba)2 (bpe)(CH3 OH)] n ·1.25H2 O (1 ) and [Cu2 ( p -brba)4 (bpe)2 Cu( p -brba)2 (bpe)(CH3 OH)] n ·1.25H2 O (2 ) (H2 p -clba = para -chlorobenzoic acid, H2 p -brba = para -bromobenzoic acid and bpe = 1, 2-bis(4-pyridyl)ethylene) have been synthesized and characterized by X-ray structure analysis. In the solid-state structure, both the compounds undergo X⋯π (X = Cl or Br) interactions to generate two-dimensional (2D) supramolecular architectures. Here, due to the larger size and better polarisability of the Br atom, the Br⋯π interaction is stronger than the Cl⋯π interaction, which accounts for the stronger interchain interactions in 2 as compared to 1 . This is depicted in the observed electrical conductivity of the compounds. Compound 2 with stronger interchain interactions shows better charge transport and hence, increased conductivity.